Southey Versus London: Proto-Romantic Disaffection and Dehumanisation in the British Metropolis - Sangster, Matthew (Romanticism on the Net, 2017)
This article explores Robert Southey’s attitudes to London, using his often negative reactions as a means of examining his construction of his identity while also employing his works as a prism through which to consider the social and representational problems that the late-eighteenth and early-nineteenth-century city presented for literary writers. It places Southey’s handful of London-related poems in the context of his wider oeuvre by analysing his correspondence, his Letters from England (1807), and the Colloquies (1829). Through looking at consonances with works by William Wordsworth, Samuel Taylor Coleridge, and Edmund Burke, among others, the article shows how Southey constructed a vision of London as a place of perverted sublimity, where scale and repetition served to grind down confidence in one’s individual value, leading to sickness, disaffection and alienation. While examining fluctuations in Southey’s attitudes over time, it contends that his fear of the London mob, his distaste at urban pollution, and his disgust at the condition of the poor remained relatively constant over the course of his career, causing him to develop attitudes to the metropolis that shaped both his own later conservatism and larger Romantic ideologies that positioned cities as uncongenial environments for the comfortable operation of poetical minds.